Further Results on Sum *Number and Mod Sum* Number of Graphs - Samal, R. K; Mishra, D (International Journal of Computer Sciences and Engineering, 2018)
In this paper we establish that the graphs K_n-E(K_r ), K_(n ,n) for n ≥2, K_(n ,n)-E(〖nK〗_2 ) for n ≥2, P_n⨀K_1 for n ≥2 and C_n⨀K_1 for n ≥4 possesses sum* and modsum* labelings and find their sum * and mod sum* numbers.